2013
DOI: 10.1128/mmbr.00051-12
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Processes of Microbial Community Assembly

Abstract: SUMMARY Recent research has expanded our understanding of microbial community assembly. However, the field of community ecology is inaccessible to many microbial ecologists because of inconsistent and often confusing terminology as well as unnecessarily polarizing debates. Thus, we review recent literature on microbial community assembly, using the framework of Vellend (Q. Rev. Biol. 85 :183–206, 2010) in an effort to synthesize and unify these contributions. We b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,279
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,458 publications
(1,318 citation statements)
references
References 156 publications
(188 reference statements)
31
1,279
2
6
Order By: Relevance
“…Probability of dispersing is not linked to other traits in the model (for example, competitive ability), and did not vary among taxa in any deterministic way. Although studies have found that some microbial life forms are more easily dispersed than others (for example, spores), most microorganisms are likely to disperse passively over large areas (Martiny et al, 2006;Nemergut et al, 2013).…”
Section: Dispersalmentioning
confidence: 99%
See 2 more Smart Citations
“…Probability of dispersing is not linked to other traits in the model (for example, competitive ability), and did not vary among taxa in any deterministic way. Although studies have found that some microbial life forms are more easily dispersed than others (for example, spores), most microorganisms are likely to disperse passively over large areas (Martiny et al, 2006;Nemergut et al, 2013).…”
Section: Dispersalmentioning
confidence: 99%
“…Because microbes have high dispersal rates, large population sizes, fast growth rates and a propensity for dormancy, communities were traditionally thought to assemble deterministically. However, recent characterizations of microbial communities provide evidence that in addition to environmental selection, stochastic processes can be important drivers of microbial community assembly (Ferrenberg et al, 2013;Nemergut et al, 2013;Zhou et al, 2013;Fukami, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community assembly processes could be divided into four main forces: dispersal, diversification, ecological drift and selection (Nemergut et al 2013). Recently, many research groups have investigated the importance of selection in determining community assembly in the rhizosphere and the phyllosphere (Bulgarelli et al 2013;Müller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial community assembly, like all ecological community assembly, is mediated by the forces of selection, dispersal, diversification, and drift (Nemergut et al., 2013; Vellend, 2010). In many ways, microbial assembly resembles plant primary succession (Fierer, Nemergut, Knight, & Craine, 2010), but the impact of dormancy and rapid evolution, as well as the immense diversity of microbes, can elicit unique patterns.…”
Section: Discussionmentioning
confidence: 99%